Arabic Mistake on Rafiq TV's YouTube Channel and Arabic Language Development in South Korea - Nisa', Mauidlotun; Roup, Mumin; Zahra Setiawan, Autia; Shodiq, Muhammad (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2025)
The development of Arabic in South Korea is now highlighted, especially since there are many course institutions and even Arabic study programs in the gingseng country. This study aims to evaluate Arabic subtitle writing errors on Rafiq TV's YouTube Channel content. The primary source of this research is the video content of Rafiq TV in UAE episodes 1-3 entitled (سافر كوريون إلى الإمارات) (كوريون في العين), and (المقبلة مع فاطمة من الإمارات). The process of this research begins with the collection of word clarification by paying attention to errors in the writing of subtitle text in the TSu and errors in pronunciation that result in changes in the intended meaning of the TSa, such as errors in the writing of words الأمارات which should be الإمارات and spelling mistake in word و دهبنا the correct word should be و ذهبنا. There are pronunciation errors such as وذهبنا is pronounced as وذهمنا. The display of Arabic subtitles in the video is also an effort to compare the writing and sound of the wrong source text. The content of Rafiq TV's YouTube channel shows that South Koreans' development of Arabic language studies is good, and even Rafiq and his friends show their skills and skills in conducting Arabic interactions in the digital space on a massive scale.